2005
DOI: 10.1016/j.molcel.2005.06.027
|View full text |Cite
|
Sign up to set email alerts
|

The Bromodomain Protein Brd4 Is a Positive Regulatory Component of P-TEFb and Stimulates RNA Polymerase II-Dependent Transcription

Abstract: Brd4 is a mammalian bromodomain protein that binds to acetylated chromatin. Proteomic analysis revealed that Brd4 interacts with cyclinT1 and Cdk9 that constitutes core positive transcription elongation factor b (P-TEFb). Brd4 interacted with P-TEFb in the living nucleus through its bromodomain. About half of P-TEFb was bound to the inhibitory subunit and functionally inactive. Brd4 interacted with P-TEFb that was free of the inhibitory subunit. An increase in Brd4 expression led to increased P-TEFb-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
1,140
2
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,131 publications
(1,190 citation statements)
references
References 38 publications
42
1,140
2
6
Order By: Relevance
“…S6A, bars 1-3). Importantly, these effects were counteracted by coexpressing siRNA against Brd4, an integral component of transcriptionally active P-TEFb (13,14), suggesting that the enhanced EDA inclusion levels were P-TEFb-dependent (Fig. 3C and Fig.…”
Section: Disintegration Of 7sk Snrnp Promotes Alternative Splicing VImentioning
confidence: 99%
See 1 more Smart Citation
“…S6A, bars 1-3). Importantly, these effects were counteracted by coexpressing siRNA against Brd4, an integral component of transcriptionally active P-TEFb (13,14), suggesting that the enhanced EDA inclusion levels were P-TEFb-dependent (Fig. 3C and Fig.…”
Section: Disintegration Of 7sk Snrnp Promotes Alternative Splicing VImentioning
confidence: 99%
“…Therein, 7SK is a molecular scaffold, which binds HEXIM1, HEXIM2, and LARP7 directly, enabling the sequestration and repression of P-TEFb. Another major fraction of P-TEFb constitutes the Brd4/P-TEFb complex, which represents the transcriptionally active P-TEFb and could be recruited to target genes because of the binding of Brd4 to acetylated histones or the mediator (13,14). The dynamic partitioning of P-TEFb between the complexes constitutes a functional equilibrium that can be perturbed.…”
mentioning
confidence: 99%
“…Binding of CCNT1, NFkB1, DDX6 and HEXIM1 was validated by co-immunoprecipitation experiments Characterization of the oncogenic AF4-MLL complex A Benedikt et al (Figure 2c, panels I-IV). For the validation of NPM1 and BRD4, full-length NPM1 and a 80 kDa fragment of BRD4Fknown to still confer binding to P-TEFb 24 Fwere both fused to GFP. This was necessary because wild-type BRD4 migrates in the SDS-PAGE at a similar position as AF4.…”
Section: Composition Of the Af4 And Af4-mll Protein Complexmentioning
confidence: 99%
“…14 Bound BRD4 stimulates the P-TEFb kinase function, facilitates binding of the AF4 complex to chromatin and prevents binding of HEXIM1. 24,33 Of interest, BRD4 binds to the acetylated NFkB1/RELA (K310) and functions as specific co-activator of NFkB1/RELA to regulate transcription of a subset of NFkB1-responsive inflammatory genes 34, and has been described as binding partner of NPM1. NFkB1/NPM1 heterodimers …”
Section: Characterization Of the Oncogenic Af4-mll Complex A Benediktmentioning
confidence: 99%
“…This methodology not only allowed us to identify Rrp1b as a dual ECM and metastasis efficiency modifier, but also to demonstrate that the cell growth regulator Bromodomain 4 (Brd4) [15][16][17], which also binds Sipa1, has similar properties with regards to metastasis and ECM gene expression (Bromodomain 4 activation predicts breast cancer survival; N.Crawford, J.Alsarraj, L.Lukes, R.Walker, H.Yang, M.Lee, K. Ozato, K.Hunter; PNAS, in press). Furthermore, we demonstrated that differential activity of BRD4 in primary breast cancers accurately predicts outcome in five different tumor gene expression datasets.…”
Section: Introductionmentioning
confidence: 99%